De L'éclaircissement sur le sacrifice de Joseph de Maistre à la 'révélation' de Durkheim. Issue 1 (1st December 2022) - de Balanda, Flavien Bertran; Béra, Matthieu
Abstract: This article examines how the counter-revolutionary writer Joseph de Maistre (1753–1821) theorizes the notion of sacrifice. For de Maistre sacrifice understood as punishment is foundational to all societies. Durkheim used many of this author's works without citing them. At the time Durkheim was teaching his criminal sociology course on punishment and responsibility as well as preparing his course on religion dealing with 'revelation'. It is possible to explain his interests by the fact that de Maistre appears in Durkheim's core readings for theoretical 'juncture' that featured authors concerned with the articulation between questions of penal law and of religious phenomena. This provides additional evidence that for Durkheim religion is at the origin of the definition of the crime and of the establishment of the punishment. Résumé: Cet article examine comment l'essayiste contre-révolutionnaire Joseph de Maistre (1753–1821) théorise la notion de sacrifice: pour lui, le sacrifice est compris comme une peine et il est à l'origine de toutes les sociétés. Or Durkheim fit usage de plusieurs de ses livres sans jamais les citer. Alors qu'il dispensait son cours de sociologie criminelle sur la peine et la responsabilité, et préparait sans doute aussi le cours sur la religion, dit 'de la révélation', il emprunta l'essai sur le sacrifice de de Maistre. On peut expliquer cet intérêt par le fait que De Maistre fait partie des lectures spéciales de 'charnière' théorique, qui renvoient à des auteurs se situant à l'articulation des questions de droit pénal et des phénomènes religieux repérés par Durkheim. On peut aussi, en conséquence, y voir une preuve de plus que, pour Durkheim, la religion est à l'origine de la définition du crime et de l'établissement de la peine.